Preparation method and application of Ru-FeOOH / NF integrated electrocatalyst for oxygen evolution by electrolyzing water
By using a step-by-step hydrothermal synthetic method on foam nickel to adorns the RU-Feooh composite catalyst, the problem of cumbersome steps in the existing technology, uneven catalyst dispersion, and low catalytic performance are solved. Large -scale production.
Patent Information
- Application Number
- CN202411963486.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The preparation steps of existing electrolytic oxygen-analyzed catalysts are complicated, the catalyst is dispersed unevenly, and the catalytic performance is low, making it difficult to achieve large-scale application.
The simple step water heating synthesis method is adopted to grow RU-Feooh composite catalyst in situ on the foam nickel nickel to achieve the uniform dispersing and efficient catalytic of the catalyst.
The uniform dispersing and efficient catalytic of the catalyst is achieved, and the performance and energy conversion efficiency of electrolyte oxygen are improved, which is suitable for large -scale production.
Smart Images

Figure CN119352093A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalytic reaction of oxygen evolution by electrolysis of water, and specifically relates to a preparation method and application of a Ru-FeOOH / NF integrated electrocatalyst for oxygen evolution by electrolysis of water. Background Art
[0002] Oxygen evolution reaction (OER) is one of the key steps in the process of hydrogen production from water electrolysis, and its efficiency directly affects the energy conversion efficiency of the entire water electrolysis process. Existing OER catalysts such as RuO2 and IrO2 have been widely studied due to their excellent catalytic performance, but their high cost limits their large-scale application. Therefore, the development of low-cost, high-performance non-precious metal catalysts has become a hot topic in current research.
[0003] As a transition metal hydroxide, iron oxyhydroxide (FeOOH) shows great potential in the electrolytic oxygen evolution reaction due to its abundant active sites and good stability. However, the catalytic activity of pure FeOOH still needs to be improved. As a porous metal support, nickel foam (NF) is widely used as a support for electrode materials due to its good conductivity, high specific surface area and excellent mechanical properties. At present, some studies have reported methods of loading FeOOH on nickel foam and improving its electrolytic oxygen evolution performance by doping Ru elements. However, these methods generally have defects such as cumbersome preparation steps, uneven catalyst dispersion and low catalytic performance. For example, a common method is to first grow FeOOH on nickel foam by chemical deposition, and then dope Ru elements into FeOOH by impregnation. However, this method has the following problems: First, it is difficult to control the morphology and distribution of FeOOH during the growth of FeOOH by chemical deposition, resulting in poor dispersion of the catalyst; second, when doping Ru elements by impregnation, the distribution of Ru elements in FeOOH is uneven, and it is easy to form agglomerations, which affects the catalytic performance. Another method is to grow Ru-FeOOH composite catalyst directly on nickel foam by electrochemical deposition. Although this method can complete the preparation of catalyst in one step, it is difficult to accurately control the ratio of Ru and Fe and the morphology of the catalyst during electrochemical deposition, resulting in unstable catalytic performance. Summary of the invention
[0004] The purpose of the present invention is to solve the problems existing in the prior art such as complicated preparation steps, uneven catalyst dispersion, low catalytic performance, etc., and proposes a preparation method and application of a Ru-FeOOH / NF integrated electrocatalyst for electrolysis of water and oxygen evolution. The method in situ grows a Ru-FeOOH composite catalyst on nickel foam by a simple one-step hydrothermal synthesis method, thereby achieving uniform dispersion of the catalyst and efficient catalysis.
[0005] The technical solution of the present invention is: A method for preparing a Ru-FeOOH / NF integrated electrocatalyst for electrolyzing water and oxygen evolution comprises the following steps: (1) Immerse the nickel foam in an acetone solution for ultrasonic cleaning for 5 to 30 min to remove oil and impurities on the surface. Place the cleaned nickel foam in a 1 to 3 mol / L hydrochloric acid solution for ultrasonic cleaning for 5 to 30 min to remove oxides on the surface. Then, place the cleaned nickel foam in deionized water for ultrasonic cleaning for 5 to 30 min. Place the cleaned nickel foam in a vacuum dryer at 40 to 70 °C for 6 to 16 h for later use. (2) dissolving an iron salt and a ruthenium salt in a molar ratio of (0.1-5):(0.01-0.5) in deionized water, then adding a certain amount of hydrogen peroxide thereto, stirring evenly to obtain a mixed solution; (3) placing the mixed solution of step (2) and the nickel foam treated in step (1) at a temperature of 90-130°C for hydrothermal reaction for 5-12 hours; then naturally cooling to room temperature, ultrasonically washing the nickel foam after the reaction with a deionized water-ethanol mixed solution, and vacuum drying to obtain a Ru-FeOOH / NF electrocatalyst.
[0006] Furthermore, in step (1), the nickel foam is pretreated by first forming a 2 × 3 cm 2 The nickel foam was immersed in acetone for 10 min and then ultrasonically treated in 1 mol / L dilute hydrochloric acid for 10 min and then ultrasonically treated in deionized water for 10 min. The nickel foam was dried in a vacuum oven at 60 °C for 12 h and set aside.
[0007] Furthermore, in step (2), the molar ratio of the iron salt to the ruthenium salt is 10:1.
[0008] Furthermore, the iron salt in step (2) is FeSO4·7H2O, the ruthenium salt is RuCl3·3H2O; the hydrogen peroxide is 30% by mass of H2O2; Weigh 0.1-5 mmol FeSO4·7H2O, 0.01-0.5 mmol RuCl3·3H2O and 0.1 mL-5 mL 30% H2O2 respectively, dissolve them in water, and stir evenly to obtain a solution.
[0009] Further, 1 mmol FeSO4·7H2O, 0.1 mmol RuCl3·3H2O, and 1 mL 30% H2O2 were dissolved in 14 mL deionized water and stirred well.
[0010] Furthermore, in the step (3), the mixed solution and the nickel foam are quickly transferred to a polytetrafluoroethylene high-pressure sealed reactor, placed in a forced air drying oven, and reacted at 100°C for 6 hours; the nickel foam after the reaction is ultrasonically washed 3 to 4 times with a deionized water-ethanol mixed solution with a volume ratio of 1:1, and then dried in a vacuum oven at 40 to 70°C for 6 to 16 hours to obtain a Ru-FeOOH / NF electrocatalyst.
[0011] The present invention also protects the use of the Ru-FeOOH / NF electrocatalyst prepared by any of the preparation methods described above in electrolysis of water.
[0012] Furthermore, the electrocatalyst is used as a working electrode to catalyze the oxygen evolution reaction in the process of alkaline water electrolysis or alkaline medium water electrolysis to produce hydrogen.
[0013] Beneficial effects of the present invention: (1) The preparation method of the Ru-FeOOH / NF integrated electrocatalyst for oxygen evolution by electrolysis of water provided by the present invention has the advantages of simple preparation steps and easy operation, and is suitable for large-scale production; the prepared catalyst has excellent performance in oxygen evolution by electrolysis of water, high energy conversion efficiency, and long life of oxygen evolution by electrolysis of water, and is expected to be widely used in the field of hydrogen production by electrolysis of water in the future.
[0014] (2) The present invention first removes oil stains and oxides on the surface of nickel foam by pretreatment, and then grows a Ru-FeOOH composite catalyst in situ on the nickel foam by a wet chemical method; during the growth process, the uniform growth and efficient catalysis of the catalyst are achieved by precisely controlling parameters such as the concentration of the reactants, reaction time and temperature.
[0015] The present invention prepares a three-dimensional structure stacked by two-dimensional sheet structures, the catalyst is evenly dispersed, the active area of the catalyst can be greatly increased, the oxygen evolution performance of the electrolyzed water is improved, the oxygen evolution performance of the electrolyzed water is stable, the bonding force between the catalyst and the electrode is strong, and the service life is long. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 A scanning electron microscope (SEM) image of the Ru-FeOOH / NF catalyst prepared in Example 1 of the present invention; Figure 2 A transmission electron microscope (TEM) image of the Ru-FeOOH / NF catalyst prepared in Example 1 of the present invention; Figure 3The high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) image and elemental surface scan image of the Ru-FeOOH / NF catalyst prepared in Example 1 of the present invention; wherein (a) is a full-view HAADF-STEM image, (b) is an enlarged image of region A in Figure (a), (c) is a surface scan image of the O element, (d) is a surface scan image of the Fe element, and (e) is a surface scan image of the Ru element; Figure 4 X-ray photoelectron spectroscopy (XPS) diagram of the Ru-FeOOH / NF catalyst prepared in Example 1 of the present invention; wherein (a) is the Fe 2p spectrum, and (b) is the Ru 3p spectrum; Figure 5 The linear sweep voltammetry curve (LSV curve) of water electrolysis and oxygen evolution of the Ru-FeOOH / NF catalyst prepared in Example 1 of the present invention; Figure 6 This is a test curve of the stability of oxygen evolution in electrolysis of the Ru-FeOOH / NF catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In order to further understand the present invention, the present invention will be further described in conjunction with the accompanying drawings and embodiments.
[0019] Example 1 This embodiment provides a method for preparing a Ru-FeOOH / NF integrated electrocatalyst for electrolysis of water and oxygen evolution, comprising the following steps: (1) Pre-treat the nickel foam by first forming a 2 × 3 cm 2 The nickel foam was immersed in an acetone solution for 10 minutes for ultrasonic treatment, and then the cleaned nickel foam was placed in 1 mol / L dilute hydrochloric acid for 10 minutes for ultrasonic treatment, and then in deionized water for 10 minutes for ultrasonic treatment, and then dried in a vacuum oven at 60°C for 12 hours for use; (2) Dissolve 1 mmol FeSO4·7H2O, 0.1 mmol RuCl3·3H2O and 1 mL H2O2 (mass fraction 30%) in 14 mL deionized water and stir well to form a mixed solution; (3) The mixed solution and the pretreated nickel foam were quickly transferred to a 25 mL polytetrafluoroethylene reactor, placed in a forced air drying oven, reacted at 100 °C for 6 h, and then naturally cooled to room temperature; the reacted nickel foam was ultrasonically washed three times with a deionized water-ethanol mixed solution with a volume ratio of 1:1, and then dried in a vacuum oven at 60 °C for 12 h to obtain the Ru-FeOOH / NF electrocatalyst.
[0020] The prepared Ru-FeOOH / NF electrocatalyst was tested by scanning electron microscopy, and the following results were obtained: Figure 1 As shown in the SEM image, it can be seen that the Ru-FeOOH / NF catalyst presents a three-dimensional structure of two-dimensional layer stacking.
[0021] The prepared Ru-FeOOH / NF electrocatalyst was tested by transmission electron microscopy, and the following results were obtained: Figure 2 The TEM image shown further illustrates that the Ru-FeOOH / NF catalyst presents an ultra-thin layer structure.
[0022] The prepared Ru-FeOOH / NF electrocatalyst was subjected to high-angle annular dark field scanning transmission electron microscopy test and element surface scanning test, and the following results were obtained: Figure 3 HAADF-STEM and elemental surface scan shown. Figure 3 The HAADF-STEM images in (a) and (b) further illustrate that the Ru-FeOOH / NF catalyst exhibits an ultra-thin layer structure. Figure 3 The element surface scans in (c), (d) and (e) show that Fe, Ru and O elements are evenly distributed on the nickel foam skeleton, indicating that the prepared catalyst is relatively uniform.
[0023] Figure 4 The XPS spectrum of Ru-FeOOH / NF catalyst is shown in Figure 2. Figure 4 As can be seen in (a), Fe 2p 3 / 2 and Fe 2p 1 / 2 The peaks are located at 710.64 and 724.49 eV, corresponding to trivalent Fe. Figure 4 As can be seen in (b), Ru 2p 3 / 2 and Ru2p 1 / 2 The peaks are located at 462.70 and 484.98 eV, respectively, corresponding to trivalent Ru.
[0024] Test Example 1 The Ru-FeOOH / NF electrocatalyst prepared in Example 1 is used to catalyze the oxygen evolution reaction in the process of alkaline water electrolysis or alkaline medium water electrolysis to produce hydrogen, and the application method is as follows: The electrochemical experiments were conducted at room temperature using a Shanghai Chenhua CHI 660E electrochemical workstation. A conventional three-electrode system was used: Ru-FeOOH / NF electrocatalyst was used as the working electrode, mercuric oxide electrode was used as the reference electrode, carbon rod was used as the counter electrode, the electrolyte was 1 M KOH solution, and the current density of the chronoamperometric-time stability test was 100 mA / cm 2 .
[0025] Figure 5 The LSV curve of Ru-FeOOH / NF catalyst for oxygen evolution in water electrolysis is shown in the figure. It can be seen that at a current density of 100 mA cm -2 When , the overpotential of Ru-FeOOH / NF is only 240 mV, which is significantly lower than the overpotential of FeOOH / NF catalyst (349 mV), indicating that Ru-FeOOH / NF catalyst has excellent OER activity.
[0026] Figure 6 This is the chronoamperometric-time stability test diagram of the Ru-FeOOH / NF catalyst. It can be seen from the figure that after 100 hours of long-term operation, the current density changes very little, indicating that the Ru-FeOOH / NF catalyst has excellent stability in alkaline electrolytes.
[0027] Example 2 This embodiment provides a method for preparing a Ru-FeOOH / NF integrated electrocatalyst for electrolysis of water and oxygen evolution, comprising the following steps: (1) Pre-treat the nickel foam by first forming a 2 × 3 cm 2 The nickel foam was immersed in an acetone solution for 5 minutes for ultrasonic treatment, and then the cleaned nickel foam was placed in a 2 mol / L dilute hydrochloric acid solution for 5 minutes for ultrasonic treatment, and then in deionized water for 5 minutes for ultrasonic treatment, and then dried in a vacuum oven at 40°C for 16 hours for use; (2) Dissolve 0.1 mmol FeSO4·7H2O, 0.01 mmol RuCl3·3H2O and 0.1 mL H2O2 (mass fraction 30%) in 14.9 mL deionized water and stir to form a mixed solution; (3) The mixed solution and the pretreated nickel foam were quickly transferred to a 25 mL polytetrafluoroethylene reactor, placed in a forced air drying oven, reacted at 90 °C for 12 h, and then naturally cooled to room temperature; the reacted nickel foam was ultrasonically washed three times with a deionized water-ethanol mixed solution with a volume ratio of 1:1, and then dried in a vacuum oven at 40 °C for 16 h to obtain the Ru-FeOOH / NF electrocatalyst.
[0028] Example 3 This embodiment provides a method for preparing a Ru-FeOOH / NF integrated electrocatalyst for electrolysis of water and oxygen evolution, comprising the following steps: (1) Pre-treat the nickel foam by first forming a 2 × 3 cm 2 The nickel foam was immersed in an acetone solution for 30 minutes of ultrasonic treatment, and then the cleaned nickel foam was placed in 3 mol / L dilute hydrochloric acid for 30 minutes of ultrasonic treatment, and then in deionized water for 30 minutes of ultrasonic treatment, and then dried in a vacuum oven at 70°C for 6 hours for use; (2) Dissolve 5 mmol FeSO4·7H2O, 0.5 mmol RuCl3·3H2O and 5 mL H2O2 (mass fraction 30%) in 10 mL deionized water and stir well to form a mixed solution; (3) The mixed solution and the pretreated nickel foam were quickly transferred to a 25 mL polytetrafluoroethylene reactor, placed in a forced air drying oven, reacted at 130 °C for 5 h, and then naturally cooled to room temperature; the reacted nickel foam was ultrasonically washed four times with a deionized water-ethanol mixed solution with a volume ratio of 1:1, and then dried in a vacuum oven at 70 °C for 6 h to obtain the Ru-FeOOH / NF electrocatalyst.
[0029] The above description is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, modification, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a Ru-FeOOH / NF integrated electrocatalyst for electrolysis of water for oxygen evolution, characterized in that: The steps include: (1) Immerse the nickel foam in an acetone solution and ultrasonically clean it for 5 to 30 min. Place the cleaned nickel foam in a 1 to 3 mol / L hydrochloric acid solution and ultrasonically clean it for 5 to 30 min. Then, ultrasonically clean it in deionized water for 5 to 30 min. Then, vacuum dry it at 40 to 70 °C for 6 to 16 h for later use. (2) dissolving an iron salt and a ruthenium salt in a molar ratio of (0.1-5):(0.01-0.5) in deionized water, then adding a certain amount of hydrogen peroxide thereto, stirring evenly to obtain a mixed solution; (3) placing the mixed solution of step (2) and the nickel foam treated in step (1) at a temperature of 90-130° C. for hydrothermal reaction for 5-12 h; ultrasonically washing the nickel foam after the reaction with a deionized water-ethanol mixed solution, and vacuum drying to obtain a Ru-FeOOH / NF electrocatalyst.
2. The preparation method according to claim 1, characterized in that: The step (1) pre-treats the nickel foam by first forming a 2 × 3 cm 2 The nickel foam was immersed in acetone for 10 min and then ultrasonically treated in 1 mol / L dilute hydrochloric acid for 10 min and then ultrasonically treated in deionized water for 10 min. The nickel foam was dried in a vacuum oven at 60 °C for 12 h and set aside.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the iron salt to the ruthenium salt in step (2) is 10:
1.
4. The preparation method according to claim 1, characterized in that: The iron salt in step (2) is FeSO4·7H2O, and the ruthenium salt is RuCl3·3H2O; the hydrogen peroxide is 30% H2O2 by mass; Weigh 0.1-5 mmol FeSO4·7H2O, 0.01-0.5 mmol RuCl3·3H2O and 0.1 mL-5 mL 30% H2O2 respectively, dissolve them in water, and stir evenly to obtain a solution.
5. The preparation method according to claim 4, characterized in that: Dissolve 1 mmol FeSO4·7H2O, 0.1 mmol RuCl3·3H2O and 1 mL 30% H2O2 in 14 mL deionized water and stir well.
6. The preparation method according to claim 1, characterized in that: In the step (3), the mixed solution and the nickel foam are quickly transferred to a polytetrafluoroethylene high-pressure sealed reactor, placed in a forced air drying oven, and reacted at 100°C for 6 hours; the nickel foam after the reaction is ultrasonically washed 3 to 4 times with a deionized water-ethanol mixed solution with a volume ratio of 1:1, and then dried in a vacuum oven at 40 to 70°C for 6 to 16 hours to obtain a Ru-FeOOH / NF electrocatalyst.
7. Use of the Ru-FeOOH / NF electrocatalyst prepared by the preparation method according to any one of claims 1 to 6 in electrolysis of water.
8. The use according to claim 7, characterized in that: The electrocatalyst is used as a working electrode and is applied to catalyze the oxygen evolution reaction in the process of alkaline water electrolysis or alkaline medium water electrolysis to produce hydrogen.
Citation Information
Patent Citations
Pd nanoparticle-loaded ferronickel double hydroxide nanosheet array structure material, preparation method and application thereof
CN111871426A
Method for preparing nickel-based catalysts with different functions based on solution supersaturation degree regulation and control
CN117344333A